The Down-Regulation of lncRNA PCAT18 Promotes the Progression of Gastric Cancer via MiR-107/PTEN/PI3K/AKT Signaling Pathway - Chen, Ping (Onco Targets Ther, 2019)
PURPOSE: LncRNAs are important regulators in cancers. In this study, we investigated the role of lncRNA PCAT18 in gastric cancer (GC). PATIENTS AND METHODS: The level of PCAT18 in GC tissues and cells was determined by qRT-PCR. The cellular behaviors of GC cells with knockdown or overexpression of PCAT18 were respectively detected by CCK-8 assays, colony formation assays, flow cytometry and Western blot. A GC mice model was established by subcutaneous injection of MGC-803 and HGC-27 cells with the knockdown or overexpression of PCAT18. The tumor size and weight were measured, and IHC was performed to determine ki-67 level. Predicted by bioinformatics software and confirmed by dual-luciferase reporter assay, PCAT18 was involved in miR-107/PTEN axis, thus, the expression of and relationship among PCAT18, miR-107 and PTEN pathway were explored in clinical cases and GC cell lines. Rescue assay was performed in GC cells by co-transfection with miR-107 mimic or PCAT18. The PTEN/PI3K/AKT pathway was then detected by Western blot. RESULTS: PCAT18 was down-regulated in GC tissues and cells, and it had a significant diagnostic value for GC. The expression of PCAT18 was highly associated with tumor size, and PCAT18 was found to inhibit GC growth in vitro and in vivo. It was also found that PCAT18 was involved in PTEN/PI3K/AKT signaling pathway through targeting miR-107. CONCLUSION: PCAT18 inhibits the progression of GC via miR-107/PTEN/PI3K/AKT signaling pathway. Additionally, PCAT18 is possibly a promising target for treatment of GC.